Effects of the Development of Central Bank Digital Currencies on Financial Markets amid the Pandemic - Kosov, Mikhail; Borisova, Lyudmila; Popkov, Sergey; Kiseleva, Tatyana; Ponkratov, Vadim; Volkova, Maria; Vatutina, Larisa; Kuznetsov, Nikolay; Dzusova, Svetlana; Mazzorana, Florie (Emerging Science Journal, 2023)
The study determined the influence of the Central Bank Digital Currency (CBDC) on the financial markets during the COVID-19 pandemic. It investigated if the CBDC had the potential to improve the efficiency and lending power of the financial system. The research relied on secondary data from a range of financial markets, such as the FTSE, MSCI, Gold Index, S&P 500, and Dow Jones, collected during the COVID-19 period. The quantitative approach was employed using the statistical software SPSS to perform descriptive statistics and regression analysis. The results revealed that the financial markets were negatively impacted by COVID-19, but the CBDC saw a higher level of development during the same period. The statistical analysis showed a positive and significant relationship between the CBDC Attention Index, the Uncertainty Index, and various financial market indices, with regression analysis indicating a significant impact of the CBDC Attention Index on all financial market indices except the Gold Index. However, this study has some limitations, including its limited scope of financial markets. Despite this, these results have important implications for academics and policymakers. It is recommended to increase the use of CBDC through well-crafted policies and legislation to fully realize its potential impact on the financial system. Doi: 10.28991/ESJ-2023-SPER-013 Full Text: PDF